Cerclage Pessary for Preventing Preterm Birth in Women with a Singleton Pregnancy and a Short Cervix at 20 to 24 Weeks: A Randomized Controlled Trial - Hui, Shuk Yi Annie; Chor, Chung Ming; Lau, Tze Kin; Lao, Terence T.; Leung, Tak Yeung (American Journal of Perinatology, 2013)
Objective To determine the effectiveness of cerclage pessary in the prevention of preterm birth in asymptomatic Chinese women with a short cervix at 20 to 24 weeks.Methods Low-risk women carrying singleton pregnancies were screened with transvaginal ultrasound, and those with a cervical length <25 mm at 20 to 24 weeks were recruited into a randomized controlled trial, comparing the prophylactic use of cerclage pessary with expectant management. The analysis was by intent-to-treat. The primary outcome measure was preterm delivery before 34 weeks.Results Among 4438 screened women, 203 women (4.6%) met the inclusion criteria and 108 (58%) consented for the study. A total of 53 and 55 women were allocated to pessary and control groups, respectively. There was no difference in background demographics, including the mean cervical length (19.6 mm versus 20.5 mm) and the mean gestational age at randomization (both 21.9 weeks). Delivery before 34 weeks occurred in 9.4% and 5.5% (p = 0.46) in the pessary and the control groups, respectively. No differences in major side effects were noted between the groups.Conclusion In our population, <5% had a cervical length of less than 25 mm at 20 to 24 weeks' gestation. The prophylactic use of cerclage pessary did not reduce the rate of preterm delivery before 34 weeks.
Keywords: cerclage pessary; short cervix; preterm birth